A review: Evolution of branching T-junction geometry in terms of diameter ratio, to improve phase separation - Faheem Ejaz; William Pao; Mohammad Shakir Nasif; Ahmed Saieed; Zeeshan Q. Memon; Md Nuruzzaman (Engineering Science and Technology, an International Journal, 2021)
T-junction is broadly utilized for phase separation, as it has a notable function as a conduit to distribute fluid, due to its simple design, low maintenance cost and adaptability to offshore industries. The geometrical parameters that influence phase separation make the phase re-distribution unpredictable. Even though the diameter ratio of the T-junction has a prominent effect on phase separation, it was not thoroughly and comprehensively reviewed specifically. This review article intends to fill in that gap, focusing solely on the effect of the diameter ratio on phase separation, specifically for two-phase flow in branching T-junction. Initially, the inversely proportional relation between diameter ratio and phase separation is discussed, reported first in the 1970s. Besides, a critical analysis in 1998, is reported which challenged the inverse proportionality. Unfortunately, their disagreement was not addressed for more than a decade. Lastly, two different criteria to determine the separation efficiency, state-of-the-art T-junction design and side arm modifications are summed up with conclusions. The primary contribution of this research is that it takes into account the agreement and disagreements among the researchers for inverse proportionality between phase separation and diameter ratio, including some critical findings that were not reported in the past in review articles. Some recommendations for future research in this domain are also reported.